The land â€â€of SUSHEN â€“ an early proto-state entity in the far east - yacheslav G. Shvedov, V; V. Stelmah, Elena; B. Golub, Andrey; A. Merdeeva, Tatyana; Ya. Dubey, Olesya; V. Nikolaev, Sergey (International Journal of Engineering and Technology, 2018)
The region of the Amur River basin and Maritime Territory (Primorye), located within the Russian Federation and the Chinese Peoples Republic, still waits to be deeply explored in order to create a coherent picture of its early historical development. This article is dedicated to the reconstruction of processes related to the establishment by the end of the 3rd or the beginning of the 2nd millennium BC and further existence of the union of tribes that lived on this territory, known as the Land of Sushen. We have identified its historical location. We have also compiled a description of the socio-economic and political environment of the Sushen tribes, examined specific characteristics of their ethnic composition and internal organizational structure and have given an assessment of their military capacity and capabilities. On the basis of a consolidated comparison of archaeological data and historical documents, we have analysed the territorial interests of the tribes of the Land of Sushen and their relationships with neighbours in the surrounding geographic areas. We have also disclosed the nature of their relations with ancient China and ancient Korea and explained their specific character. We have reconstructed the causes for the military defeat suffered by the Sushen from Central Asian nomads and its consequences. We have determined their subsequent ethnic heritage in the Amur region and Primorye. Â Â